2023
DOI: 10.46303/jcsr.2023.26
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Heads of Departments’ Infusion of Ubuntu Values in Curriculum and Knowledge Sharing Leadership in Under-Resourced Public Schools

Abstract: The article reports on the findings of a qualitative inquiry involving a sample of nine (9) teachers (three participants per school) drawn from three schools within the locality of three education circuits of Emalahleni in Mpumalanga Province (South Africa). The primary objective of the article was informed by the paucity of literature that establishes an intersection between Indigenous epistemologies of Ubuntu philosophy, instructional leadership and the sharing process of knowledge management within the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Kalema et al (2016) found that Senior teachers hoarded tacit knowledge instead of transferring it to their novice or mid-career counterparts, as they were of the view that giving away too much knowledge would render them powerless and replaceable. Doing so denies novice and midcareer teachers a wealth of tacit knowledge that rests in Senior teachers' minds (Nkambule, 2023b). Rismark and Sølvberg (2011) further point out that teachers who do not share knowledge with their peers are a barrier to their respective schools' aspirations to become learning organisations.…”
Section: Individuals In Organisationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kalema et al (2016) found that Senior teachers hoarded tacit knowledge instead of transferring it to their novice or mid-career counterparts, as they were of the view that giving away too much knowledge would render them powerless and replaceable. Doing so denies novice and midcareer teachers a wealth of tacit knowledge that rests in Senior teachers' minds (Nkambule, 2023b). Rismark and Sølvberg (2011) further point out that teachers who do not share knowledge with their peers are a barrier to their respective schools' aspirations to become learning organisations.…”
Section: Individuals In Organisationsmentioning
confidence: 99%
“…It is a challenge to get everyone's buy-in on certain processes and procedures, the management is at times, resistant to change and tends to be loyal to their old ways, especially the knowledge that comes from new/younger teachers. Leader's failure to motivate, reward and recognise workers ' [i.e., teachers] knowledge sharing efforts (Šajeva, 2014) exposes their lack of knowledge leadership skills (Kazak, 2021;Nkambule, 2023b).…”
Section: C)mentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, "the cornerstone of the ToC is the application of the correctly calibrated combination of capacity building (support) with accountability (pressure)" (Fullan, 1999cited in Fleisch, 2023. In the parlance of school management, accountability and capacity building refer to the availability of a series of workshops, follow-ups and briefings, study, reflections, field observations (Morake, 2014), mentorship, peer coaching, coaching clinics, seminars, and conferences as well as informal short-term courses and in-service post-graduate training (Nkambule, 2020(Nkambule, , 2023b. Meanwhile, his mentioning of "accountability (pressure)" Fullan (1999cited in Fleisch, 2023 serves to highlight the importance of having school leaders who can learn to adapt their leadership approaches to different situations and to use their personalities to influence the achievement of high performing, interdisciplinary teams that thrive in a culture of continuous learning focused on school improvement (New South Wales Government [NSW], 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%